A dynamic approach for emergency decision making based on prospect theory with interval-valued Pythagorean fuzzy linguistic variables. (May 2019) - Ding, Xue-Feng; Liu, Hu-Chen; Shi, Hua
Highlights: A dynamic approach is proposed in this paper for emergency decision making. The uncertain assessment information of decision makers is handled by IVPFLVs. The weights of criteria are calculated by a combination weighting method. An extended prospect theory is applied to rank emergency decision solutions. The practicability of proposed approach is illustrated by an empirical example. Abstract: Emergency events can bring huge economic losses and casualties to human beings if not properly managed. To reduce all kinds of losses and prevent the escalation of disasters, it is of great importance to make reasonable decisions for emergencies in the short time. In the emergency decision making (EDM), however, decision information is often vague and uncertain and most of the current decision methods assume that decision makers are completely rational. Accordingly, this paper presents a dynamic approach based on interval-valued Pythagorean fuzzy linguistic variables (IVPFLVs) and prospect theory, called dynamic IVPFL-PT, for dealing with the EDM problems. First, the fuzzy assessments of decision makers are represented as IVPFLVs, and the weights of criteria are obtained by using a combination weighting method. Then, the prospect theory which can describe the psychological behaviors of decision makers is applied to rank emergency solutions. Furthermore, the proposed EDM approach can determine the best solution dynamically under different status. The new dynamic IVPFL-PT approach is implemented in a real example and compared with existing methods to demonstrate its feasibility and practicability.